TANTANGAN GEREJA DALAM MELAYANI PENDERITA GANGGUAN MENTAL DI GEREJA TORAJA JEMAAT FILADELFIA KONDONGAN - Tumonglo, Esther Epin (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2022)
Everyone has the potential to experience mental disorders, both at mild and severe levels. People with mental disorders experience disturbances in thoughts, behaviors, and feelings that are manifested in the form of a set of symptoms or changes in behavior and can cause suffering and obstacles in carrying out people's functions as humans. The church has a vocation to minister to people with mental disorders so that they can live worthy lives in the image of God and be healed. However, to carry out this ministry, the church faces various obstacles. This study explores the church's challenges in serving people with mental disorders. The research subject is the Toraja Church of the Filadelfia Kondongan Congregation in Tana Toraja, South Sulawesi. The research method used is qualitative. There were six informants: one pastor, three church councils, and two family members of the sufferer. Data were collected by interviewing techniques and analyzed using reduction, display, and conclusion. The study results indicate that the current challenge is the lack of knowledge and understanding of mental disorders, which has resulted in not formulating and implementing concrete programs for people with mental disorders in the congregation.